COMPARATIVE ANALYSIS OF AMPUTATION OF LOWER LIMBS IN CRITICAL ISCHEMIA IN PATIENTS WITH DIABETES MELLITUS (DM) - B. B. Safoyev; A. Ya. Rakhimov (Galaxy International Interdisciplinary Research Journal, 2022)
A retrospective analysis was made of the case histories of 58 patients with diabetes who underwent abdominal amputation in the surgical department on the basis of the "General Surgery" department of the Bukhara State Medical Institute during 2014-2017. Depending on the surgical tactic, all patients are divided into 2 groups: in the first (n = 31) performed a high amputation, in the 2 nd group (n = 27) amputation at the level of the shank by Mitisha. An analysis of the results showed that amputation at the tibia at Mitish is a more effective method, while the mortality rate is reduced to 5%, the disability is up to 44%.